Analisis Kesiapan Implementasi Kebijakan Tes Kemampuan Akademik (TKA) 2025 oleh Kemendikbud - Juriyah, Juriyah; Fahrudin, Tomulyo; Jalaludin, Jalaludin (YASIN, 2025)
Indonesia’s educational assessment reform has entered a new phase with the introduction of the 2025 Tes Kemampuan Akademik (TKA), in response to the abolition of the National Examination (UN) and the redefined function of the National Assessment (AN), which now focuses on system-level evaluation rather than individual performance. This study aims to analyze the readiness level for implementing the TKA 2025 policy prior to its nationwide rollout. A qualitative method was employed using a descriptive policy analysis design, guided by George C. Edward III’s policy implementation framework, which comprises four key variables: communication, resources, disposition, and bureaucratic structure. Data were drawn from secondary sources, including regulatory documents, official socialization materials, and national media coverage, and analyzed thematically. The findings reveal varying levels of readiness across the dimensions. The bureaucratic structure appears procedurally mature, owing to prior experience with the National Assessment. In terms of disposition, stakeholder enthusiasm—particularly among students—is high, as the TKA will serve as a university admissions tool. However, implementation readiness remains hindered by limited resources, notably the digital infrastructure gap between developed and underdeveloped regions. Furthermore, although policy communication has been relatively effective in disseminating information, a paradox emerges: the test is voluntary yet high-stakes, potentially generating anxiety among student participants. The study concludes that the successful implementation of TKA 2025 will largely depend on the state’s ability to bridge resource disparities and align policy communication in an inclusive and consistent manner.